Facing the Enemy - Mills, DiAnn (Carol Stream, IL : Tyndale House Publishers, 2023)
"When the long-awaited reunion between Risa and her brother, Trenton, ends in tragedy, Risa is riddled with guilt, unable to cope with the responsibility she feels over his death. On leave from the FBI, Risa returns to her former career as an English teacher at a local college, only to see her past and present collide when one of her students, Carson Mercury, turns in an assignment that reads like an eyewitness account of her brother's murder, with details never revealed publicly. Alarmed by Carson's inside knowledge of Trenton's death, Risa reaches out to her former partner at the FBI. Special Agent Gage Patterson has been working a string of baby kidnappings, but he agrees to help look into Carson's background. Risa and Gage soon discover their cases might be connected as a string of high-value thefts have occurred at properties where security systems were installed by Carson's stepfather and children have gone missing. There's a far more sinister plot at play than they ever imagined, and innocent lives are in danger"--Provided by publisher.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction. -- Employees; Murder -- Fiction. -- Investigation; Missing children -- Fiction; Brothers -- Fiction. -- Death; College teachers -- Fiction; Texas -- Fiction; Detective and mystery fiction; Christian fiction; Thrillers (Fiction); Novels; Fiction